The effect of the gender equality on income inequality : a dynamic panel approach - Baloch, Amdadullah; Zaleha Mohd Noor,; Muzafar Shah Habibullah,; Nor Yasmin Mhd Bani, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the effects of gender equality on income inequality along with several dimensions of gender equality using panel data of 103 countries for the period of 2006-13. We use the dynamic econometric method system Generalized Method of Moments (Sys-GMM) to explore the link between these two variables. The empirical evidence shows a negative and significant impact of gender equality and its sub-indices on income distribution, suggesting that by increasing equality between males and females will result in lower income inequality. GDP per capita has nonlinear effect income inequality. Education attainment has a negative effect on income distribution, while higher inflation rate increases income inequality. This analysis implies that by narrowing the gender gap or increasing equality between males and females will effectively contributes to expanding equality in income.